2014
DOI: 10.1091/mbc.e13-10-0564
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of telomere associations by TRF1 cleavage in mouse embryonic stem cells

Abstract: This study provides novel insight into the formation and resolution of telomere associations, which have been observed during key cellular processes such as mitosis, meiosis, and carcinogenesis. TRF1, a core component of the telomere protein complex, is a mediator of telomere associations in mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Interestingly, we also observed the localization of TRF1 connecting telomeres of two or more chromosomes (Figure 2Bb white arrow) or in fused telomeres (Figure 2Bb, blue arrow). This pattern of localization has been described at telomeres when unbalanced levels of TRF1 are present (Lisaingo et al 2014) and resembled the telomeric defects we previously reported using FISH (Martinerie et al 2014). These results showed that levels of TRF1 at the telomeres were not affected by deficiency of E-type cyclins, but its localization pattern might be affected, forming stretches of DNA and bridges between chromosomes.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, we also observed the localization of TRF1 connecting telomeres of two or more chromosomes (Figure 2Bb white arrow) or in fused telomeres (Figure 2Bb, blue arrow). This pattern of localization has been described at telomeres when unbalanced levels of TRF1 are present (Lisaingo et al 2014) and resembled the telomeric defects we previously reported using FISH (Martinerie et al 2014). These results showed that levels of TRF1 at the telomeres were not affected by deficiency of E-type cyclins, but its localization pattern might be affected, forming stretches of DNA and bridges between chromosomes.…”
Section: Resultssupporting
confidence: 87%
“…Although TRF1 does not contribute significantly to the end protection functions of the Shelterin complex (Zimmermann et al 2014), it plays a key role in maintaining telomere length, and in the formation of telomere associations in mitosis and meiosis (Cooper et al 1998; Miller et al 2006). It has been further shown that unbalanced levels of TRF1 in telomeres, produced by experimental overexpression or observed in cancer cells, results in telomeric bridges and aggregates containing TRF1 protein and telomeric DNA (Lisaingo et al 2014; Munoz et al 2009). We have previously reported that one of the most striking meiotic phenotypes observed in E-type cyclin deficient spermatocytes is a high frequency of telomeric bridges between non-homologous chromosomes (Martinerie et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaphase bridges are found among cells exhibiting impaired telomere homeostasis [39][40][41][42] and defective DNA DSB repair. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] RINT1 is known to be involved in both pathways through interaction with p130 15 or Rad50. 14 The structure of chromosome fusion in the Rint1-deficient cells supports the hypothesis of defective DSB repair (Figures 4c and d).…”
Section: Discussionmentioning
confidence: 99%
“…Increased telomere length may promote melanoma formation by delaying telomere‐driven senescence in melanoma precursor lesions, such as ‘dysplastic’ nevi. Increased telomere length may itself drive telomere genomic instability by promoting chromosome mis‐segregation and aneuploidy through effects on mitosis . Finally, heterogeneous or increased telomere length might simply be a marker of telomere uncapping, which would be the primary driver of genomic instability and aneuploidy .…”
Section: Discussionmentioning
confidence: 99%